المرکز القومى للترجمة : دراسة ببلیوجرافیة ببلیومتریة - د. شیماء فاروق شعلان (المجلة الدولية لعلوم المكتبات والمعلومات)
This study limits, describes and analyzes. The translated intellectualproduction published in the national center for translation in Egypt since itsinception in 2007 to 2014 there were 1105 translated books have been observedwith their objective and linguistic trends, and were chronologically distributed inorder to know the size of the translated intellectual production of national centerfor translation.